5‐Aminolevulinic acid‐Loaded Fullerene Nanoparticles for In Vitro and In Vivo Photodynamic Therapy. (1st July 2014) - Li, Zhi; Pan, Li‐Li; Zhang, Fei‐Long; Zhu, Xia‐Li; Liu, Yang; Zhang, Zhen‐Zhong
Abstract This report explores some properties of 80–200 nm nanoparticles containing 5‐aminolevulinic acid (ALA) and fullerene (C60) for photodynamic therapy (PDT). Compared with ALA, the nanoparticles yielded more protoporphyrin IX (PpIX) formation in cells and tissues and to a significant improvement in antitumor efficacy in tumor‐bearing mice. Maximum levels of PpIX were obtained 4 h after administration and selective PpIX formation in tumor was observed. These nanoparticles appear to be a useful vehicle for drug delivery purposes. In this study, a procedure for preparing fullerene nanoparticles containing ALA was developed. The product alone exhibited no detectable toxicity in the dark and was superior to ALA alone in promoting PpIX biosynthesis and PDT efficacy both in culture and in a murine tumor model. These results suggest that this procedure could be the basis for an improved PDT protocol for cancer control.